2004
DOI: 10.1093/nar/gkh187
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear antisense effects in cyclophilin A pre-mRNA splicing by oligonucleotides: a comparison of tricyclo-DNA with LNA

Abstract: The nuclear antisense properties of a series of tricyclo (tc)-DNA oligonucleotide 9-15mers, targeted against the 3' and 5' splice sites of exon 4 of cyclophilin A (CyPA) pre-mRNA, were evaluated in HeLa cells and compared with those of corresponding LNA-oligonucleotides. While the 9mers showed no significant antisense effect, the 11-15mers induced exon 4 skipping and exon 3+4 double skipping to about an equal extent upon lipofectamine mediated transfection in a sequence- and dose-dependent manner, as revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 41 publications
(40 reference statements)
4
41
0
Order By: Relevance
“…According to previously reported data [34,35], several regions of both exons were analyzed with regard to recognizing exon splicing enhancer in addition to the donor/acceptor splice sites and allowing the skipping of targeted exons. After AON treatment of normal human myoblasts, RT-PCR analysis encompassing exons 22 and 23 was performed using a combination of primers located from exon 20 to exon 26 to ensure amplification of shorter fragments carrying an exon 22-23 deletion or larger ones, as described in previous studies [36,37]. We observed several skipped products corresponding to deletions of exon 23 alone, exons 22 and 23, exons 22-24, or exon 24 alone (Fig.…”
Section: Patient Phenotype and Genotype Descriptionsupporting
confidence: 56%
See 1 more Smart Citation
“…According to previously reported data [34,35], several regions of both exons were analyzed with regard to recognizing exon splicing enhancer in addition to the donor/acceptor splice sites and allowing the skipping of targeted exons. After AON treatment of normal human myoblasts, RT-PCR analysis encompassing exons 22 and 23 was performed using a combination of primers located from exon 20 to exon 26 to ensure amplification of shorter fragments carrying an exon 22-23 deletion or larger ones, as described in previous studies [36,37]. We observed several skipped products corresponding to deletions of exon 23 alone, exons 22 and 23, exons 22-24, or exon 24 alone (Fig.…”
Section: Patient Phenotype and Genotype Descriptionsupporting
confidence: 56%
“…For each transfection condition, 1 lg RNA was retrotranscribed, and 80 ng cDNA was used as the matrix for the first PCR program. Primers were located in exons 20 (fwd) and 26 (rev) in order to amplify shorter fragments carrying an exon 22-23 deletion or larger ones, as sometimes observed in previous studies [16,37]. A second semi-nested PCR, using an internal forward primer located in exon 21 and the same reverse primer (exon 26), was performed using 2 lL of PCR product from the first PCR.…”
Section: Aon Design and Efficiency Testsmentioning
confidence: 99%
“…In several in vitro test systems, antisense oligonucleotides have proven to be highly successful in correcting aberrant splicing brought about by ␤-globin gene in thalassemia and the cystic fibrosis transmembrane conductance regulator gene (Friedman et al, 1999). Until now only two published studies have used this antisense approach to target premRNA and selectively splice out specific exons (Karras et al, 2000;Ittig et al, 2004). The Karras et al (2000) study reported that constitutive/alternative splicing of murine interleukin-5 receptor-␣ (IL-5R␣) chain pre-mRNA can be modulated in cells using specific antisense morpholino oligo- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the affinity of single strand ligand towards single strand RNA various other successful modifications have been carried out in the past [19][20][21][22][23][24][25][26][27] . Recent candidates of such chemically modified oligonucleotide analogs include HNA 28 , locked nucleic acid (LNA) 29,30 , 2′-MOE-RNA and related 2′-O-modified RNA 31 , PNA and modifications thereof 32 , Morpholino-NAs 33 and tricyclo-DNA [34][35][36] . Earlier we have shown that disulphide bond containing oligodeo xynu-cleotide stabilizes triplex structure 41,42 as well as DNA: DNA double helix structure 43 .…”
Section: Introductionmentioning
confidence: 99%